Consumption Values, Attitude, Place Identity, Dan Place Dependence Sebagai Anteseden Revisit Intention (Studi Pada Pengunjung Street Food Di Kota Bandung) - Fina Syaidah; Yadi Ernawadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study was to examine the factors that affect revisit intention Lengkong street food visitors as many as 100 respondents have experienced eating food in Lengkong street food Bandung. The cross-sectional method is used to obtain data. The instrument passed the validity and reliability tests which include convergent validity, discriminant validity, and composite reliability. The data analysis technique used is structural equation modeling (SEM) using Smart-PLS version 3.0. Of the 10 proposed research hypotheses, 9 of them are supported by empirical data. The findings of this study show that taste value, price value, social value, emotional value, and epistemic value have a positive effect on attitude. Then, attitude has a positive effect on revisit intention through place identity and place dependence. The results of this study are expected to provide benefits for further research and the management of the assessed object or similar culinary industry related to the design of relevant strategies to improve the quality of these attributes. The thing that distinguishes this study from previous research is the addition of place identity and place dependence as the antecedent of revisit intention. Researchers are further advised to explore other factors that may influence revisit intention. Keywords: Taste Value, Health Value, Price Value, Social Value, Emotional Value, Epistemic Value, Attitude, Place Identity, Place Dependence, and Revisit Intention.